2017
DOI: 10.1021/acs.energyfuels.7b02788
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Coker Coke Characterization: Correlation between Process Conditions, Coke Composition, and Morphology

Abstract: Delayed coking is the technology most used to upgrade vacuum residue into high-value products, but in this process, secondary reactions produce coke. It is already known that the chemical and physical properties and composition of the feedstock and processing conditions affect coke morphology. Recently, a new type of morphology, called transition coke, has been described, but this morphology should be avoided because it induces operational and safety risks to delayed coking units. Several studies have attempte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…This comparison should be considered qualitative because the coke characterizations reported in Table were from industrial samples and were not accompanied by characterizations of the bitumen feed materials. Nevertheless, similar observations can be found for other oils where the feed and coke from delayed coking were both characterized in the same study …”
Section: Technologies For Partial Upgradingsupporting
confidence: 83%
See 1 more Smart Citation
“…This comparison should be considered qualitative because the coke characterizations reported in Table were from industrial samples and were not accompanied by characterizations of the bitumen feed materials. Nevertheless, similar observations can be found for other oils where the feed and coke from delayed coking were both characterized in the same study …”
Section: Technologies For Partial Upgradingsupporting
confidence: 83%
“…Nevertheless, similar observations can be found for other oils where the feed and coke from delayed coking were both characterized in the same study. 64 Delayed coking is inherently associated with a yield loss due to the formation of coke and light gases. For Athabasca bitumen, typical coke and gas yields are around 25 and 3 wt %, respectively.…”
Section: Technologies For Partial Upgradingmentioning
confidence: 99%
“…Table 4. The results of FTIR analysis of carbon fillers [49][50][51][52][53][54][55]. It was also found that during grinding the PET coke was broken down into rather irregular solid crumbs, while the CP coke grains disintegrated mainly along carbon planes giving flake-shaped particles (Figure 3).…”
Section: Characteristics Of Carbon Fillersmentioning
confidence: 99%
“…Without the S-crosslinker, the carbon yield is only 5 wt%, with a s.a. o10 m 2 g À1 . 23 the complexity of the feed and the crosslinked intermediate presents challenges to derive mechanism. A key analytical breakthrough came from 1H NMR and GPC.…”
mentioning
confidence: 99%